THE EFFECT OF OLDER PEOPLE’S ADAPTATION TO OLD AGE ON THEIR HEALTH-RELATED QUALITY OF LIFE - Aşiret, Güler Duru; Yiğit, Havva (LIFE: International Journal of Health and Life-Sciences, 2018)
The changes that occur with age affect the older people’s quality of life. This study aimed at determining the effect of older people’s adaptation to old age on their health-related quality of life. This descriptive study was conducted with 250 older people that applied to the outpatient clinics of the Research and Training Hospital of Aksaray University between the dates of 15 January and 15 June 2017. The study data were collected by using an introductory information form, “Assessment Scale of Adaptation Difficulty for the Elderly (ASADE)” and “Nottingham Health Profile (NHP)”. The study data were assessed by using descriptive statistical methods, Mann Whitney U, Kruskal Wallis, Spearman Correlation Test and multilinear regression model. This study found that older people’s adaptation to old age and their health-related quality of life were at a good level. As their score from ASADE increased, their score from NHP increased (r=0.742, p<0.001). In addition, adaptation to old age, gender and expressed health status had a statistically significant on the quality of life (p<0.005). We suggest that the health personnel assess adaptation to old age, which is one of the factors affecting the quality of life, and increase the quality of life by conducting interventions to increase the adaptation to old age.